Energy-Aware Fault Tolerant Task offloading of Mobile Cloud Computing - Abd S.K.; Al-Haddad S.A.R.; Hashim F.; Abdullah A.B.H.J.; Yussof S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bioinformatics; Cloud computing; Digital storage; Energy efficiency; Energy utilization; Mobile devices; Mobile telecommunication systems; Power management; Computational task; Fault-tolerant; Processing time; Scheduling techniques; Storage capability; Task offloading; Task-processing; Time management; Mobile cloud computing